Peran dan Kontribusi Ayat-Ayat Muhkam dan Mutasyabih dalam Pembentukan Corak Teologi Islam - Putri Ayu Ramadhani; Halimah Basri; Nasrullah Bin Sapa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Research on muhkam and mutasyabih verses in the Qur‘an has been widely carried out. However, no research looks at the theological aspects historically on the implications of understanding the two forms of the verse. The muhkam verse which is qath‘i dalalah implies the birth of the basic aqidah. While the mutasyabih verse which is zhanni dalalah has implications for the birth of a branch aqidah. Based on the different understandings and interpretations of the two, the historical facts of Muslims have given birth to various opinions and schools of thought. Inevitably also cause a crisis because of cross opinion. The verse mutasyabih is misinterpreted with a narrow understanding and one interpretation. While the muhkam verse is the basis for its legitimacy. There needs to be a broad perspective in dealing with this problem. Muslims who are plural and have different intellectual capacities must be able to cultivate an attitude of tolerance for different views. The paradigm of fanatical thinking must be abandoned over branch issues. Unity must be prioritized as a starting point in building the people in pluralism. This article will examine these issues. This research is library research by looking at the historical facts that exist and using clear literature. The method used in this research is descriptive-analytical and comparative so that it can reveal the mistakes that occur among the people and see the actual comparison. The goal is to create a sense of tolerance for differences and uphold the values of equality and unity among the people.